Structural Equation Modeling of Gastronomic Tourism in the Face of COVID-19 - Arger Verstapp Bund; Gilberto Bermúdez Ruíz; Olga Anaid Diaz Jacinto; Alfredo Barrera Escobar; Celia Yaneth Quiroz Campas; Rosa María Rincón Ornelas; Francisco Espinoza Morales; Cruz García Lirios; Gregorio Elizarraraz Guarneros (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The pandemic has claimed the lives of seven million, affecting the local economy. Anti-COVID-19 policies promote entrepreneurship as a central axis of the economic agenda. In the case of tourism, micro-financing policies encourage the local economy through the promotion of magical towns. The gastronomy trade has benefited from fiscal and monetary incentives. In this sense, the objective of this work was to establish the determinants of innovative entrepreneurship with a sample of 100 merchants. A predictive model was contrasted in which resource optimization determined product innovation. In relation to the state of knowledge, the scope and limits of the study were discussed.